Estimation of longitudinal force, lateral vehicle speed and yaw rate for four-wheel independent driven electric vehicles. (15th February 2018) - Chen, Te; Xu, Xing; Chen, Long; Jiang, Haobing; Cai, Yingfeng; Li, Yong
Highlights: A longitudinal force observer is designed based on adaptive high-order sliding mode observer. A strong tracking filter is used to estimate lateral vehicle speed and yaw rate. A co-simulation is carried out to demonstrate the effectiveness of the proposed method. Abstract: Accurate estimation of longitudinal force, lateral vehicle speed and yaw rate is of great significance to torque allocation and stability control for four-wheel independent driven electric vehicle (4WID-EVs). A fusion method is proposed to estimate the longitudinal force, lateral vehicle speed and yaw rate for 4WID-EVs. The electric driving wheel model (EDWM) is introduced into the longitudinal force estimation, the longitudinal force observer (LFO) is designed firstly based on the adaptive high-order sliding mode observer (HSMO), and the convergence of LFO is analyzed and proved. Based on the estimated longitudinal force, an estimation strategy is then presented in which the strong tracking filter (STF) is used to estimate lateral vehicle speed and yaw rate simultaneously. Finally, co-simulation via Carsim and Matlab/Simulink is carried out to demonstrate the effectiveness of the proposed method. The performance of LFO in practice is verified by the experiment on chassis dynamometer bench.